School of Economics and Management, Taishan University, Taian, China - Yang, Xiaoyan (Journal of Theory and Practice of Contemporary Education, 2023)
In the 1970s, Illich published the book "Deschool Society", in which he criticized the deceptive nature of school education at that time and for the first time proposed the idea of abolishing schools in a more radical manner. However, even today, we can see that schools still exist, and with the further development of the knowledge economy, schools will continue to develop. Therefore, from a practical perspective, Illich's proposal to abolish schools is absurd. However, there is also rationality behind absurdity, which has enlightening significance for us to think about the respective positioning and roles of schools, education, and teachers today, how to view the many relationships between schools and education, diplomas and abilities, and people and technology. Therefore, this article takes Illich's idea of de institutionalization as a clue to explore the rationality behind his absurdity, in order to provide some reflections for today's education.